Program of functional instruction in reading comprehension of poems in elementary school students - Néstor Miguel Velarde Corrales; Aldo Bazán-Ramírez (Interacciones)
The purpose of the present study was to develop reading comprehension skills of poems in sixth grade students of a public rural school in the State of Morelos, Mexico, who had low levels of achievement indicators, at the end of the fifth curricular block of the program of sixth grade of primary, called Leer y escribir poemas para compartir. A prior evaluation of the group showed that 28 of the 30 students had a low level of reading comprehension, therefore, it was formed in a random manner, a group of eleven students who took a training course for reading comprehension, which consisted of six sessions. A pre- and post-treatment analysis showed that the 11 children exposed to the training improved their performance in reading activities. Likewise, the data showed that the development of the competence to understand literary texts (poems) are configured hierarchically according to the levels of functional aptitude and their criteria of achievement.